The Effect of ESG Ratings on Firm Performance with ESG Rating Disagreement as The Moderating Variable - Azaria Nabila; Susi Sarumpaet (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) ratings on firm performance and the moderating role of ESG rating disagreement within the Indonesian capital market. Using a panel dataset of 63 companies listed on the Indonesia Stock Exchange from 2021 to 2023 and employing a fixed-effects regression model, the analysis measures firm performance with Tobin’s Q, ESG ratings from Refinitiv Eikon, and ESG rating disagreement as the standard deviation between Refinitiv and Bloomberg scores. The empirical results indicate that ESG ratings do not have a statis-tically significant effect on firm performance, and ESG rating disagreement does not significantly moderate this relationship. These findings suggest that ESG-related information has not yet been fully internalized into firm valuation in Indonesia, with current ESG practices perceived as largely symbolic rather than substantively integrated into corporate strategy. The study concludes that both ESG ratings and rating disagreement fail to serve as effective mechanisms for enhancing firm performance in the Indonesian context, reflecting the early-stage development and compliance-driven nature of ESG adoption in emerging markets.